Detection of specific antibodies to pigeon serum and bloom antigens by enzyme linked immunosorbent assay in pigeon breeder's disease. Issue 3 (1st March 2000) - Rodrigo, M J; Benavent, M I; Cruz, M J; Rosell, M; Murio, C; Pascual, C; Morell, F
Abstract : BACKGROUND: Pigeon breeder's disease is an extrinsic allergic alveolitis in the lungs of sensitised people, caused by hypersensitivity reactions to inhaled pigeon antigens. Antigens from different sources of the animal are used for diagnostic purposes, with serum being the most widely used. Bloom is rarely used; very little is known of its antigenicity and diagnostic performance, particularly when used with the enzyme linked immunosorbent assay (ELISA) method, which is the most popular test as it permits measurement of the antibody response. METHODS: To ( a ) standardise an ELISA for the measurement of specific IgG against pigeon serum and pigeon bloom extract; ( b ) to establish reference values for specific IgG in 73 non-exposed controls, ( c ) to show the presence of specific IgG against pigeon serum and bloom in serum samples of 17 patients with bird fancier's lung and 11 asymptomatic fanciers, and ( d ) to study the similarity of the two antigen sources by cross reactivity experiments. RESULTS: Reference values of specific IgG were defined with the 97.5 percentile (367.9 U/ml for pigeon serum and 953.7 U/ml for pigeon bloom extract). Of symptomatic patients 100% had values higher than the cut off for both antigens. In asymptomatic fanciers values were higher than the cut off for pigeon serum in 45% and bloom extract in 54%. Cross reactivity experiments showed that the two antigens differed in antigenic content although some components may be common to both. CONCLUSION: The ELISA methods used proved to be useful tools for evaluating specific IgG antibody responses against both antigens. The diagnostic performance of both ELISA methods performed with these antigen sources was similar, showing very high sensitivity but moderate specificity. Although some antigenic similarity was found between pigeon serum and bloom extract, cross reactivity studies showed that various antigens seemed to be specific to the bloom extract. However, the antigens responsible for pigeon breeder's disease seem to be present in both antigenic sources.